The microbiology of chronic osteomyelitis: Changes over ten years. Issue 3 (September 2019) - Dudareva, Maria; Hotchen, Andrew James; Ferguson, Jamie; Hodgson, Susanne; Scarborough, Matthew; Atkins, Bridget L.; McNally, Martin A.
Abstract: Aim: This study quantified changes in the microbiology of osteomyelitis over a ten year period from a single centre within the UK with regard to infection with multi-drug resistant (MDR) bacteria and susceptibility of antimicrobial regimens. Method: Patients with chronic osteomyelitis undergoing definitive surgery from 2013–2017 were inluded ( n = 223). Microbiology was compared to patients in a cohort from 2001–2004, using the same diagnostic criteria, and same deep tissue sampling technique ( n = 157). Clinical features associated with MDR bacterial infection were analysed using logistic regression. Results: Both cohorts had similar baseline characteristics. Despite a similar proportion of Staphylococcus aureus in both cohorts, the rate of methicillin resistant Staphylococcus aureus (MRSA) infection was lower in 2013–2017 compared to 2001–2004 (11.4% vs 30.8% of Staphylococcus aureus, p = 0.007 ). However, the proportion of MDR infections was similar in both cohorts (15.2% versus 17.2%). Metalwork was associated with MDR infection (unadjusted OR 5.0; 95% CI: 1.15 to 22.0). There was no change in resistance to glycopeptide / meropenem combination treatment (2.2% vs 2.5%, p > 0.9). Conclusions: In this centre, rates of MRSA osteomyelitis have fallen by two thirds, over the past 10 years, in line with the reducing rate of MRSA bacteraemia nationally. A history of metalwork may predict MDR infection. A glycopeptide with an anti-pseudomonal carbapenem remains the post-operative empiric systemic regimen of choice. Resistance patterns support the use of a glycopeptide with an aminoglycoside in local antibiotic therapy.